Dampak Penggunaan Aplikasi Tiktok pada Peserta Didik Kelas VIII dan Implikasinya dalam Layanan Bimbingan dan Konseling di SMP Negeri 2 Sijunjung - Lusiana Masri; Rici Kardo; Rila Rahma Mulyani (Journal on Education, 2023)
This research looks at the phenomenon that there are still students who experience the impact of using the tiktok application. This study aims to describe 1) the positive impact of the tiktok application, 2) the negative impact of the tiktok application, 3) the implications of guidance and counseling services. The research population was students of class VIII at SMP Negeri 2 Sijunjung, totaling 180 students. Sampling using purposive sampling technique, a sample of 48 students. Sources of research data are primary data and secondary data. The data collection technique is in the form of a questionnaire and processed using a percentage technique. The results of this study reveal that in general they are in the category of students who use the tiktok application. 1) The positive impacts of using the tiktok application in general are in the many categories, 2) The negative impacts of using the tiktok application in general are in the very many categories, 3) Implications of BK services affected by users of the tiktok application are advised by researchers to conduct reality counseling. Based on the results of this study, the researcher recommends that guidance and counseling teachers pay more attention to and assist students in using applications on smartphones, especially the tiktok application so that students are able to interact with their friends at school and can follow the learning process well. It is recommended for students to reduce the use of the tiktok application in everyday life so as to avoid the negative effects arising from the application.